Bactrospora totonacae (Arthoniales, Ascomycota), a new species from Veracruz, Mexico - Guzmán-Guillermo, Jorge; Sorcia-Navarrete, Paola L.; Llarena-Hernández, Régulo C.; Cárdenas-Mendoza, Kevin Dorian R. (Instituto de Ecología, A.C., 2021)
Background and Aims: Bactrospora is a genus of crustose lichens characterized by its black, verrucose to denticulate and little apothecia, and mostly acicular, or sometimes muriform spores, longer than wide. The genus is represented by 38 accepted species. The aim of this work is to describe Bactrospora totonacae, a new species from the tropical dry forest of Veracruz, Mexico. Methods: The specimens were collected on the “Cerro de los Metates” in the municipality of Actopan, Veracruz, Mexico. Macrochemical tests, UV reaction, and a thin layer chromatography were performed; likewise, the presence of amyloid substances distributed in the thallus and ascomata was verified with Lugol’s solution. The voucher is deposited in the herbarium XALU of the Facultad de Biología of the Universidad Veracruzana. Key results: The new species Bactrospora totonacae is characterized by the pruine K+ reddish magenta in its disc. Conclusions: The described species is unique in Bactrospora because the combination of pruine K+ reddish magenta and a thick carbonized exciple has never been reported in this genus.